(untitled) (Research, Society and Development, 2022)
The objective of this work was to analyze the morphoanatomy of star anise fruits (Illicium verum Hook f.), in order to contribute to their correct botanical identification. The fruits were analyzed macroscopically and microscopically, taking into account aspects such as dehiscence, longitudinal and transverse extension in their lower and dorsal portions, considering the median region, shape and coloring of the seeds and the size of the fruits. Histochemical tests were also used to identify phenolic compounds, mucilage, pectin, lipids, starch, terpenes and oleoresins. The results showed follicles with an average size of 10 mm longitudinally and 2 mm transversally, and their dehiscence can occur on both the upper and lower surfaces. The seeds showed elliptical shape and endosperm. The external integument showed strongly lignified cells and arranged radially, longitudinally, with pits. The peduncle is stellar in shape with three projections and a vascular system consisting of a vascular cylinder with primary xylem and phloem, parenchyma cells in a transverse plane and conducting cells longitudinally. The epicarp contained elongated cells in the transverse and longitudinal planes and the mesocarp contained parenchyma cells with secretory spaces and sclereids. Histochemistry was positive for lipids and pectin. Our findings provide new data that can help in the unequivocal identification of I. verum fruits, given the scarce information available in the literature, which was discrepant in some aspects such as: the arrangement of vascular bundles and the occurrence of cavities in the mesocarp as opposed to idioblasts.